Old Drug, New Trick: Tilorone, a Broad-Spectrum Antiviral Drug as a Potential Anti-Fibrotic Therapeutic for the Diseased Heart - Duncan Horlock; David M. Kaye; Catherine E. Winbanks; Xiao-Ming Gao; Helen Kiriazis; Daniel G. Donner; Paul Gregorevic; Julie R. McMullen; Bianca C. Bernardo (MDPI AG, 2021)
Cardiac fibrosis is associated with most forms of cardiovascular disease. No reliable therapies targeting cardiac fibrosis are available, thus identifying novel drugs that can resolve or prevent fibrosis is needed. Tilorone, an antiviral agent, can prevent fibrosis in a mouse model of lung disease. We investigated the anti-fibrotic effects of tilorone in human cardiac fibroblasts in vitro by performing a radioisotopic assay for [3H]-proline incorporation as a proxy for collagen synthesis. Exploratory studies in human cardiac fibroblasts treated with tilorone (10 µM) showed a significant reduction in transforming growth factor-β induced collagen synthesis compared to untreated fibroblasts. To determine if this finding could be recapitulated in vivo, mice with established pathological remodelling due to four weeks of transverse aortic constriction (TAC) were administered tilorone (50 mg/kg, i.p) or saline every third day for eight weeks. Treatment with tilorone was associated with attenuation of fibrosis (assessed by Masson's trichrome stain), a favourable cardiac gene expression profile and no further deterioration of cardiac systolic function determined by echocardiography compared to saline treated TAC mice. These data demonstrate that tilorone has anti-fibrotic actions in human cardiac fibroblasts and the adult mouse heart, and represents a potential novel therapy to treat fibrosis associated with heart failure.